An Alarm Pheromone Modulates Appetitive Olfactory Learning in the Honeybee (Apis Mellifera) - Urlacher, Elodie; Francés, Bernard; Giurfa, Martin; Devaud, Jean-Marc (Frontiers in Behavioral Neuroscience, 2010)
In honeybees, associative learning is embedded in a social context as bees possess a highly complex social organization in which communication among individuals is mediated by dance behavior informing about food sources, and by a high variety of pheromones that maintain the social links between individuals of a hive. Proboscis extension response (PER) conditioning is a case of appetitive learning, in which harnessed bees learn to associate odor stimuli with sucrose reward in the laboratory. Despite its recurrent use as a tool for uncovering the behavioral, cellular and molecular bases underlying associative learning, the question of whether social signals (pheromones) affect appetitive learning has not been addressed in this experimental framework. This situation contrasts with reports underlining that foraging activity of bees is modulated by alarm pheromones released in the presence of a potential danger. Here, we show that appetitive learning is impaired by the sting alarm pheromone (SAP) which, when released by guards, recruits foragers to defend the hive. This effect is mimicked by the main component of SAP, isopentyl acetate (IPA), is dose-dependent and lasts up to 24h. Learning impairment is specific to alarm signal exposure and is independent of the odorant used for conditioning. Our results suggest that learning impairment may be a response to the biological significance of SAP as an alarm signal, which would detract bees from responding to any appetitive stimuli in a situation in which such responses would be of secondary importance.